“Para um lugar espaçoso” : o papel da kénosis na cristologia criacional de Jürgen Moltmann - Dall’Agnol, Renan (2023)
This research inquiries into the role of kenosis in Jürgen Moltmann's creational Christology, where the spatial amplitude is emphasized. Modern theology rejected the spatial study and heeded it exclusive to the natural sciences. However, salvation and its fruits, as justice, peace, a fulfilling life and an ecological care, don’t emerge from and anti-spatial reality. Therefore, it is intended to transform the vision that disassociates the concepts of human behavior and, with this, express the important collaboration of theological spatiality hoping for a transforming ethos. This dissertation concentrates on the systematic subject, without losing sight of the social horizon. By means of the hermeneutic method and a short reference to the foundations of the Moltmannian’s building, it is presented the basis of the living space, provided by God to its creation and the promise of a cosmic shekinah. Moltmann removes the modern conception that reduces the Trinity to the absolute subject, goes further into the creation theology and eschatology and elucidates them with an Old Testament’s indwelling notion (chapter 1). From the trinity doctrine and throughout the opening premise, the kenotic self-restriction as a plausible cosmological fundament is discussed. At the paradoxical end of Jesus Christ – the Abandoned to the absolute nothingness – at the cross, the new spatial beginning and the redemptive experiences of the current creational process emerge (chapter 2). A nod is given to the relation between science and creation, the alleged appropriation of space by the modern natural sciences is inquired and the search for an integrative space and a sapiential behavior between the knowledge areas is proposed. Following, the spatial dimension on the context of the new creation generated by the Resurrected is described, the theologian understanding of cosmological Christology and how it creates a transforming ethos on the current creation is clarified (chapter 3). Summarizing, at this discursive space the broad space, experienced by the human being, and the vitality aroused by God in each creature is emphasized. It is intended to help change the present iniquities – war, migration, ecological crisis, etc. – reinforcing the divine kenosis as the beginning of the eschatological creational transfiguration.